(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The article presents a numerical study of the collision avoidance method for mobile collaborative robots in a multi-user environment, which is a relevant task of modern robotics in the conditions of Industry 5.0. The proposed approach combines the principles of the mutual velocity obstacle model and the dynamic window method, which allows forming adaptive trajectories taking into account moving agents and static obstacles. The numerical simulation demonstrates the effectiveness of the algorithm in complex scenarios, where robots start from different positions and head towards separate targets, maintaining safe distances during interaction. The results obtained show that even in cases of critical convergence, the system is able to correct trajectories and prevent collisions. Analysis of trajectories and minimum inter-agent distances confirms the logical consistency of the algorithm and its ability to dynamically adjust. Qualitative assessment indicates that the system achieves stability at the later stages of modeling, which is confirmed by the increase in distances between agents after resolving conflict situations. Thus, the developed method can be used as a basis for building intelligent traffic control systems in a multi-user environment.